2016
DOI: 10.1080/15592324.2015.1127497
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between miRNA regulation and mechanical stress forCUCgene expression at the shoot apical meristem

Abstract: The shoot apical meristem is the central organizer of plant aerial organogenesis. The molecular bases of its functions involve several cross-talks between transcription factors, hormones and microRNAs. We recently showed that the expression of the homeobox transcription factor STM is induced by mechanical perturbations, adding another layer of complexity to this regulation. Here we provide additional evidence that mechanical perturbations impact the promoter activity of CUC3, an important regulator of boundary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…In addition to developmental and hormonal signals, microRNA posttranscriptional regulation of gene expression responds to abiotic and mechanical stress signals (Barciszewska-Pacak et al 2015;Fal et al 2016). Previously, microRNA165/166 was shown to be required for SAM activity in Arabidopsis and in maize (Zea mays) (Williams & Fletcher 2005;Chitwood et al 2009;Carlsbecker et al 2010;Chen 2012).…”
Section: Effect Of Environmental Stress On Auxin and Cytokinin Circuitsmentioning
confidence: 99%
“…In addition to developmental and hormonal signals, microRNA posttranscriptional regulation of gene expression responds to abiotic and mechanical stress signals (Barciszewska-Pacak et al 2015;Fal et al 2016). Previously, microRNA165/166 was shown to be required for SAM activity in Arabidopsis and in maize (Zea mays) (Williams & Fletcher 2005;Chitwood et al 2009;Carlsbecker et al 2010;Chen 2012).…”
Section: Effect Of Environmental Stress On Auxin and Cytokinin Circuitsmentioning
confidence: 99%
“…In the present study, mechanical stress effectively increased cell viability and promoted the osteogenic differentiation rate of OLF cells. Mechanical stimuli induce alterations in bone microstructure and produce a number of local signals, which are recognized by mechanical stress-sensitive cells (17). Li et al (18) demonstrated that mechanical strain regulates osteogenic differentiation in bone marrow stromal cells (BMSCs).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, mechanical perturbations in SAM induce the expression of the master regulators SHOOT MERISTEMLESS and CUC3 . Interestingly, the STM and CUC3 promoters are more active in the boundary of the meristem, a site of highly anisotropic stresses, thus providing a scenario in which shape‐ and growth‐derived stresses contribute to gene expression patterns in SAM (Fal et al ., ; Landrein et al ., ). It should be noted that similar conclusions have also been obtained previously in animal development (e.g.…”
Section: Evidence For a Role Of Mechanical Cues In Proprioceptionmentioning
confidence: 99%